2019
DOI: 10.29313/gmhc.v7i3.3673
|View full text |Cite
|
Sign up to set email alerts
|

Stunting Determinant on Toddler Age of 12–24 Months in Singaparna Public Health Center Tasikmalaya Regency

Abstract: Stunting is a physical growth failure condition signed by height based on age under −2SD. The research goal is knowing the dominant factor associated with stunting on toddler age of 12–24 months in the working area of Singaparna Public Health Center Tasikmalaya regency. The research applies to the cross-sectional design of gender, weight, exclusive breastfeeding history, completeness immunization, and clinically healthy variables, while case-control is for nutrition intake variable. The sample was a total samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
1
0
4
Order By: Relevance
“…Based on research, it was found that of respondents aged 20-35 years, as many as 66.7% used health services for the treatment of stunting toddlers (Sumartini et al, 2019). Current lifestyle, responsibilities and commitments depend on experience, including determining whether or not to use health services and proper nutrition when sick (Rosha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on research, it was found that of respondents aged 20-35 years, as many as 66.7% used health services for the treatment of stunting toddlers (Sumartini et al, 2019). Current lifestyle, responsibilities and commitments depend on experience, including determining whether or not to use health services and proper nutrition when sick (Rosha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Stunting terjadi sebagai dampak dari malnutrisi kronis selama 1.000 hari pertama kehidupan yang dapat disebabkan oleh bebagai faktor yaitu pendidikan kurang yang dipengaruhi oleh orangtua, apabila pendidikan orangtua tinggi berpengaruh terhadap pengasuhan dan secara langsung memberikan motivasi kepada anak untuk belajar secara optimal karena terdapat asuhan orangtua yang baik. (10)(11) Untuk memenuhi kebutuhan gizi yang cukup dapat berpengaruh pada pendapatan atau penghasilan orangtua. Penghasilan merupakan hasil dari penjualan barang dagangan, pelaksanaan kepada pelanggan atau klien untuk memperoleh penghasilan.…”
Section: Cunclassified
“…Hasil ini berbanding terbalik dengan penelitian-penelitian terdahulu. 6,[23][24][25][26][27] Jenis kelamin berhubungan dengan kejadian stunted. Anak laki-laki lebih berkemungkinan mengalami stunted daripada anak perempuan.…”
Section: Pembahasanunclassified
“…Anak lakilaki cenderung memiliki aktivitas fisik yang lebih banyak dibandingkan anak perempuan, akibatnya ia harus meproduksi energi yang lebih banyak untuk menunjang pertumbuhannya. 23,24 Usia kelahiran memengaruhi kejadian stunted. Anak yang lahir prematur lebih berisiko 2-3 kali lipat mengalami stunted dibandingkan anak dengan usia kelahiran normal.…”
Section: Pembahasanunclassified